Strategi Pemasaran di Era Digital dalam Membangun Brand Awareness Melalui Media Sosial - Yogie Alontari (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study provides an overview of marketing strategies in enhancing brand awareness through social media. Technological developments greatly affect all aspects of life and the world of marketing certainly did not escape from it all. The development of the digital world presents a new breakthrough, with the advent of social media. Social media that there is of course we can use to do activity of promotion. Promotional activities we can do is to create ads and publish via social media. And we can do promotions through social media by creating content that appeals to audiences such as creating advertisements in the form of pictures, photos, videos, moving banners and so forth, which of course should attract the attention of audiences, and if the attention of our audiences has been obtained, then will easily of course to build brand awareness to the audience of our products. We can publish ads that we make with social media that characteristics in accordance with market segmentation and targeting the market of our products. Social media can also create a new trend through social influencers that exist.